GnRH removal in the 7-11 CO-Synch for timed insemination of beef heifers - D.R. Eborn; David M. Grieger (Kansas Agricultural Experiment Station Research Reports, 2007)
The use of artificial insemination can improve genetics, shorten the calving season, and increase weaning weights by having more calves born earlier in the breeding season. Reasons that this technology has not been used by many producers may include poor conception rates, time, and cost. Research has been directed at shortening the synchronization time and controlling time of ovulation to eliminate estrous detection using a timed artificial insemination. Use of a progestin, like the Eazi-Breed CIDR or melengestrol acetate (MGA), is desirable because they are effective in synchronizing estrus and they can also induce cyclicity in anestrus or prepubertal females. In addition, gonadotropin releasing hormone (GnRH) is commonly included in a synchronization plan because it induces ovulation and synchronizes follicular development. The most common synchronization protocol for beef heifers consists of feeding MGA for 14 days, a prostaglandin injection 17 to 19 days later followed by five days of heat detection for a total duration of 36 to 38 days. Recent research suggests that acceptable conception rates can be achieved when shortening the time of MGA to seven days. One example is the 7-11 CO-Synch which is comprised of seven days of MGA feeding followed by the CO-Synch protocol starting on day 11 (see Figure 1). We have obtained greater then 60% conception rates using the 7-11 CO-Synch in previous years. The feeding of MGA not only synchronizes the estrous cycle but provides exposure to a progestin that may induce prepubertal heifers to begin cycling. The GnRH injection at day 11 should synchronize the follicular wave which will tighten the timing of ovulation and improve timed insemination conception rates. The disadvantage to this synchronization protocol is that it requires the heifers to go through the chute four times. It is also believed that heifers are less responsive to GnRH than cows. Thus we tested this protocol with or without the day 11 GnRH injection on conception rates of beef heifers.
Keywords: Cattlemen& #x27; s Day; 2007; Kansas Agricultural Experiment Station contribution; no. 07-179-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 978; Beef; Cattle; A.I.; MGA; 7-11 CO-Synch